2018
DOI: 10.1055/s-0039-1678753
|View full text |Cite
|
Sign up to set email alerts
|

Preconception Care in the Veterans Health Administration

Abstract: Preconception care (PCC), defined as a set of interventions to help women optimize their health and well-being prior to pregnancy, can improve pregnancy outcomes and is recommended by national organizations including the Centers for Disease Control and Prevention and the American College of Obstetricians and Gynecologists. Women Veterans who use the Department of Veterans Affairs (VA) health care system may face elevated risks of adverse pregnancy and birth outcomes due to a high prevalence of chronic medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Figure 1 shows MyPath, a patient-facing web-based reproductive decision support tool that we developed to promote high-quality, person-centered discussions about reproductive needs in the Veterans Health Administration (VA). Veterans capable of pregnancy who use VA Health Care services are a highly diverse population, with nearly half identifying as racial or ethnic minoritized groups [32], and face elevated risks of adverse pregnancy and birth outcomes compared to their civilian counterparts due to a higher prevalence of medical, mental health, and psychosocial factors [33]. Drawing on our first principle (Principle 1: Interdisciplinary stakeholder-inclusive teams), MyPath development was informed by formative qualitative work to understand veterans' preferences and needs [25] and followed user-centered design principles, guided by patient, provider, and scientific expert input [34].…”
Section: Reproductive Care For Nonpregnant People With Mypathmentioning
confidence: 99%
“…Figure 1 shows MyPath, a patient-facing web-based reproductive decision support tool that we developed to promote high-quality, person-centered discussions about reproductive needs in the Veterans Health Administration (VA). Veterans capable of pregnancy who use VA Health Care services are a highly diverse population, with nearly half identifying as racial or ethnic minoritized groups [32], and face elevated risks of adverse pregnancy and birth outcomes compared to their civilian counterparts due to a higher prevalence of medical, mental health, and psychosocial factors [33]. Drawing on our first principle (Principle 1: Interdisciplinary stakeholder-inclusive teams), MyPath development was informed by formative qualitative work to understand veterans' preferences and needs [25] and followed user-centered design principles, guided by patient, provider, and scientific expert input [34].…”
Section: Reproductive Care For Nonpregnant People With Mypathmentioning
confidence: 99%
“…One study found that patients with Hispanic ethnicity, higher parity, unintended pregnancy, or without insurance were less likely than their Caucasian counterparts to receive preconception counseling. 18 Another study of Hispanic and African American women demonstrated one-third of participants with chronic medical conditions was unaware of preconception health risks and, therefore, did not seek preconception care. 19 Health disparities affecting minority women has also been found to decrease these women's access to preconception counseling and management of preexisting conditions, directly affecting pregnancy outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing that Veteran women are a high-risk population, the VA should continue to strive to optimize preconception, postpartum, and interconception care. 46,47 This may mean aspiring beyond a single maternal care coordinator role to, for example, the provision of on-site integrated and multidisciplinary obstetrician-gynecologist and mental health care to address the unique needs and higher risks embodied by women Veterans. 30…”
Section: Health Systems Considerations and Guidance For Providers Carmentioning
confidence: 99%